Starting Point for Writing and Submitting Manuscripts for Publication for Junior Faculty in Academia...National Society of Allied Health Annual Conference, March 30 - April 1, 2023, Montgomery, Alabama. - Carter III, Cleve (Journal of the National Society of Allied Health)
Junior faculty teaching in allied health science programs at colleges and universities grapple with the demands of writing manuscripts for publication to earn points toward annual performance review, promotion, and tenure. It is significant that junior faculty who teach in allied health science programs become knowledgeable and/or aware of where one can start with writing and submitting manuscripts for publication. The purpose of this presentation is to inform allied health science junior faculty in higher education about a starting point for writing and submitting manuscripts for publication.